Analysis of Refusal of Inpatients by Government Hospitals Causing State Administrative Disputes - Jhouharotul Faradisah; Siti Lukmanah; Akbar DioSasqia Putra; Asmuni (Institute of Medico-legal Publications Pvt Ltd, 2021)
This research is based on the fact that in the community shows that there are still many hospitals that haven’tprovided health services to society without the element of discrimination, many mass media are preachingrejection of the patient until so that causes death. Rejection of patients in government hospitals in the formof direct action falls into the category of state administrative disputes if it is article 87 of Law number 30of 2014 concerning government administration point, which is a written determination that is also a factualaction of a government hospital. The methodology in this study uses normative juridical types as well asusing statute, conceptual, and case approach. On this research, using primary legal materials in the form ofthe Constitution, AP Law and PTUN Law.This research relates to the involvement of state administrationofficials if there is any refusal of patients at government hospitals and authority and the act of grantingdecisions without authority (Factual Actions) reviewed from the AP Law that causes material and immateriallosses towards the community. Administrative sanctions on government officials who perform factual actsthat article 81 of the AP Law, namely light, moderate, and severe administrative sanctions.